Evaluating the Impact of Financial and Economic Factors on Environmental Degradation: A Panel Estimation Study of Selected Asean Countries - Rasiah, Ratneswary; Guptan, Vinitha; Habibullah, Muzafar Shah (International Journal of Energy Economics and Policy, 2018)
Global warming is one of the most significant challenges facing the world today, as it poses an alarming threat to the entire ecosystem, human health, the economy, and national security. With the ever-increasing emission of carbon dioxide and other greenhouse gases, there has been a progressive rise in mean temperatures recorded, causing global sea levels to increase as a result of the acceleration of warming oceans, shrinking ice sheets and glacial retreat. Global warming has heightened the ferocity and frequency of extreme calamities such as heat waves, drought, wildfires, hurricanes, floods and storm surges. Extreme mitigation measures must be taken to stop this trend, failing which global warming could cause a devastating impact on the entire planet and its communities. It is imperative that more research be carried out to evaluate the impact of various factors affecting carbon emissions, as it is one of the main greenhouse gases. This study is therefore in the right direction, as it examines the long-run relationships and short-run dynamic interactions between carbon emissions and its determinants comprising of income per capita, energy use, trade openness and financial development, over the period 1970 to 2016. The study applies the dynamic heterogenous panel estimation techniques of Mean Group (MG), Pooled Mean Group (PMG) and Dynamic Fixed Effects (DFE) to analyse a set of macro panel data of the ASEAN-5 countries, to establish the possible causal relations between these variables. An analysis of the results reveal the existence of a long-run causality between carbon emissions and its explanatory variables, indicated by the significant error correction terms for all the models tested in this study. There is evidence that energy use, trade openness and per capita income significantly contribute to carbon emissions, with energy use being the most dominant contributor. Interestingly, the study also reveals that financial development is not significant in determining carbon emissions in these selected countries. The study concludes with an examination of policy implications of the findings. Keywords: Carbon emission, financial development, pooled mean group, ASEAN-5 JEL Classifications: L70, G29 DOI: https://doi.org/10.32479/ijeep.7111